O medo e os vínculos sociais no Brasil - Durand, Marina (2005)
The subject matter of this study is the link between unequal persons; organized by command-obedience relationships so as to configure the terms dominant-dominated. The link is a notion that embraces simultaneously the social relationships and the psychical process underneath them; thus it s a useful theoretical tool when the matter of the investigation are psychosocial processes. The analysis of command-obedience relationships points to the presence of elements of paternalistic culture, even in openly capitalist work relationships. The effects of this culture hit the worker s subjectivity, making more complex the effort to fight for his rights. Workers oscillate between two forms of ordination of the link; the moral one, keen to the paternalistic culture, alternates with the interest-aimed ordination, proper of the capitalist means of production. One can observe how the ideology of the work system uses emotional disposition and traditional significants in order to achieve its profit goals. There s a special interest in following some of the effects or paternalistic culture on social life, such as: the difficulty to exert authority even when one is entitled to, to stand for one s rights and to cope with corrupt authorities. There are also the subjective effects, specially the paranoid feeling, the threat represented by autonomy issues and the lowering of self-esteem, resulting of narcissistic gaps associated to the lack of public property sense. To identify with one s aggressor implies living with a negative sense of one s own ideal. One consequence is self-rejection, experienced by Brazilians as a rule. I suggest there are structural conflicts both in our subjectivity and bidding, leading us to live as first and second rate people; the answers are manifold, but each one will have to deal with this question his own way. Brazil is a name that lives within us, and the place where we live. The way by which the law is enforced by many authorities who don t represent it, but end up substituting it, intensifies the echoes of paternalistic culture. The thesis outline starts from a nucleus: the analysis of work relations among damaged workers in order to identify the processes that lead to work accidents. Furthermore, it seeks to mesurate work relations as relationships between dominant and subaltern classes, pervaded by mistrust . The social status of dependency and the subjection bond are also common terms to both situations, the enduring repressed element is the wish for autonomy, to be one s own person as opposite to be the one who serves. The analysis of the praxis from professional members of the public health system indicates the construction of a psychical and ideological organization with premises that are distinct from paternalism. Therefore, the other won t represent an opportunity to demonstrate some sort of superiority but a chance to offer the better one has to offer instead. This reciprocity might establish links, which are less sadist-masochist and more in agreement to the genital organization of the libido, that is to say, fertile to both. The diference, in this case, has no qualities added